2015
DOI: 10.1038/srep13735
|View full text |Cite
|
Sign up to set email alerts
|

FoxM1 Directs STAT3 Expression Essential for Human Endometrial Stromal Decidualization

Abstract: Human endometrium decidualization, which involves endometrial stromal proliferation and differentiation, is a prerequisite for embryo implantation, thus successful pregnancy. The Forkhead Box M1 (FoxM1), previously known as HNF-3, HFH-11, MPP2, Win, and Trident, is a transcriptional factor that plays crucial roles in cell proliferation and cell cycle progression. However, the molecular mechanism of FoxM1 during human endometrial decidualization remains unexplored. In this study, we first found FoxM1 is dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…Forkhead box protein O3A ( FOXO3A ) was shown to be down-regulated upon decidualization, whereas forkhead box protein O4 ( FOXO4 ) is not expressed in the endometrium [ 53 ]. On the other hand, we confirmed the up-regulation of STAT3 upon decidualization [ 54 ], but failed to show its regulation by insulin, suggesting that the effect of insulin was specific to FOXO1 . It was also shown that inhibition of FOXM1 could prevent decidualization [ 54 ], while insulin could not in our experiments.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Forkhead box protein O3A ( FOXO3A ) was shown to be down-regulated upon decidualization, whereas forkhead box protein O4 ( FOXO4 ) is not expressed in the endometrium [ 53 ]. On the other hand, we confirmed the up-regulation of STAT3 upon decidualization [ 54 ], but failed to show its regulation by insulin, suggesting that the effect of insulin was specific to FOXO1 . It was also shown that inhibition of FOXM1 could prevent decidualization [ 54 ], while insulin could not in our experiments.…”
Section: Discussionmentioning
confidence: 58%
“…On the other hand, we confirmed the up-regulation of STAT3 upon decidualization [ 54 ], but failed to show its regulation by insulin, suggesting that the effect of insulin was specific to FOXO1 . It was also shown that inhibition of FOXM1 could prevent decidualization [ 54 ], while insulin could not in our experiments. These observations further suggest that insulin does not inhibit the activity of FOXM1 in decidualizing stromal cells.…”
Section: Discussionmentioning
confidence: 58%
“…A recent genomic study using these cells identified P response element in the HOXA10 gene promoter, implying that HOXA10 is a direct target of PR in endometrial stromal cells . Interestingly, it has been reported recently that FoxM1 functions downstream of Hoxa10 to control stromal cell proliferation in the mouse and it directs the expression of STAT3 during human endometrial stromal cell differentiation …”
Section: Control Of Uterine Receptivity and Decidualization By Pr‐regmentioning
confidence: 99%
“…Decidualization stimuli such as oestrogen, progesterone, and cAMP specifically upregulate STAT3 [ 75 , 76 ] and STAT5 [ 71 ] in endometrial stromal cells. In vivo STAT3 is maximally expressed in glandular epithelium during the secretory phase and in decidual cells during late-secretory phase [ 76 ].…”
Section: Human Decidual Development and Structurementioning
confidence: 99%